Potential Utility of Electrical Impedance Myography in Evaluating Age-Related Skeletal Muscle Function Deficits - Clark, Brian C.; Rutkove, Seward; Lupton, Elmer C.; Padilla, Carlos J.; Arnold, W. David (Frontiers in Physiology, 2021)
Skeletal muscle function deficits associated with advancing age are due to several physiological and morphological changes including loss of muscle size and quality (conceptualized as a reduction in the intrinsic force-generating capacity of a muscle when adjusted for muscle size). Several factors can contribute to loss of muscle quality, including denervation, excitation-contraction uncoupling, increased fibrosis, and myosteatosis (excessive levels of inter- and intramuscular adipose tissue and intramyocellular lipids). These factors also adversely affect metabolic function. There is a major unmet need for tools to rapidly and easily assess muscle mass and quality in clinical settings with minimal patient and provider burden. Herein, we discuss the potential for electrical impedance myography (EIM) as a tool to evaluate muscle mass and quality in older adults. EIM applies weak, non-detectible (e.g., 400 μA), mutifrequency (e.g., 1 kHz to 1 MHz) elec¬trical currents to a muscle (or muscle group) through two excitation electrodes, and re¬sulting voltages are mea¬¬sured via two sense elec¬¬trodes. Measurements are fast, simple to perform, and unaffected by factors such as hydration that may affect other simple measures of muscle status. After nearly two decades of study, EIM has been shown to reflect muscle health status, including the presence of atrophy, fibrosis, and fatty infiltration, in a variety of conditions (e.g., developmental growth and maturation, conditioning/deconditioning, and obesity) and neuromuscular diseases states (e.g., amyotrophic lateral sclerosis and muscular dystrophies). In this article, we describe prior work and current evidence of EIM’s potential utility as a measure of muscle health in aging and geriatric medicine.